Classification of Fruit Types of Onobrychis with Machine Learning Approach - Kızgın, Mehmet Selim; Çambay, Zafer; Sepet, Hakan; Özçelik, Salih Taha Alperen; Uyanık, Hakan (Soner ÖZGEN, 2023)
In this study, the aim is to give general information about machine learning and Local Binary Pattern (LBP) and to classify sainfoin (Onobrychis) plant fruits grown in Türkiye with machine learning in the light of this information. A database was created using a total of 448 fruit images of 4 different Sainfoin (Onobrychis) species. These species are O. cappadocica, O. argyrea, O. hypargyrea and O. tournefortii, respectively. Machine learning methods were used to classify sainfoin (Onobrychis) fruit varieties. These methods were classified by four different methods, namely Support Vector Machine Method, Naive Bayes Algorithm Method, Decision Trees Method and K-Nearest Neighbor Method. The performances of these four different methods were compared and it was determined that the most suitable model was the Support Vector Machine Method with a 99.6% correct classification success rate.

Bu çalışmada amaç makine öğrenmesi ve Yerel İkili Örüntü (YİÖ) hakkında genel bir bilgi verip bu bilgi ışığında Türkiye’de yetişen korunga (Onobrychis) bitki meyvelerini makine öğrenmesi ile sınıflandırmaktır. 4 farklı Korunga (Onobrychis) türüne toplam 448 adet meyve görüntüsü kullanılarak bir veri tabanı oluşturulmuştur. Bu türler sırasıyla O. cappadocica, O. argyrea, O. hypargyrea ve O. tournefortii’ dir. Korunga (Onobrychis) meyve çeşitlerini sınıflandırmasını yapmak için makine öğrenmesi yöntemleri kullanılmıştır. Kullanılan bu yöntemler sırasıyla Destek Vektör Makinesi (DVM), Naif Bayes(NB), Karar Ağaçları (KA) ve K-En Yakın Komşu (k-EYK) olmak üzere dört farklı yöntem ile sınıflandırma işlemi yapılmıştır. Bu dört farklı yöntemin pe rformansları karşılaştırılıp en başarılı modelin %99,6 doğru sınıflandırma başarı oranı ile Destek Vektör Makinesi Yöntemi olduğu belirlenmiştir.
Onobrychis Bitkisine Ait Meyve Tiplerinin Makine Öğrenmesi Yaklaşımıyla Sınıflandırılması
Keywords: Machine Learning Algorithms; Makine Öğrenmesi Algoritmaları; Classification Algorithms; Sınıflandırma algoritmaları